2008
DOI: 10.1038/sj.bjc.6604333
|View full text |Cite
|
Sign up to set email alerts
|

Adverse prognosis of epigenetic inactivation in RUNX3 gene at 1p36 in human pancreatic cancer

Abstract: Alteration in transforming growth factor-b signalling pathway is one of the main causes of pancreatic cancer. The human runt-related transcription factor 3 gene (RUNX3) is an important component of this pathway. RUNX3 locus 1p36 is commonly deleted in a variety of human cancers, including pancreatic cancer. Therefore, we examined genetic and epigenetic alterations of RUNX3 in human pancreatic cancer. Thirty-two patients with pancreatic cancer were investigated in this study. We examined the methylation status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
1
14
2
1
Order By: Relevance
“…The methylation of the RUNX3 gene is an important mechanism by which RUNX3 protein expression is down-regulated or even lost. The inhibition of RUNX3 expression is correlated with some clinicopathologic parameters, and RUNX3 gene methylation is significantly correlated with tumor development and prognosis [22][23][24][25][26]. Nonetheless, we found no significant relationship between the methylation of the RUNX3 gene CpG island and clinicopathologic parameters, such as sex, age, clinical stage, nerve invasion, lymph node transfer, and metastasis.…”
Section: Discussioncontrasting
confidence: 62%
“…The methylation of the RUNX3 gene is an important mechanism by which RUNX3 protein expression is down-regulated or even lost. The inhibition of RUNX3 expression is correlated with some clinicopathologic parameters, and RUNX3 gene methylation is significantly correlated with tumor development and prognosis [22][23][24][25][26]. Nonetheless, we found no significant relationship between the methylation of the RUNX3 gene CpG island and clinicopathologic parameters, such as sex, age, clinical stage, nerve invasion, lymph node transfer, and metastasis.…”
Section: Discussioncontrasting
confidence: 62%
“…It was demonstrated that rUnX3 methylation was significant correlated with clinicopathological parameters, such as clinical stage, nerve invasion, lymph node metastasis and distant metastasis; however, no correlation with gender, age, tumor site and histologic types was noted. these results are consistent with those in the literature which report that 'RUNX3 methylation has significant correlation with tumor progression and prognosis' (12,(51)(52)(53)(54). the degree of rUnX3 methylation in 19 cases of frozen Acc specimens was significantly related with the down-regulation of mRNA and protein of RUNX3, suggesting RUNX3 methylation may be a key mechanism for RUNX3 inactivation in the genesis and progression of Acc.…”
Section: Discussionsupporting
confidence: 82%
“…RUNX3 is unique in that it is inactivated primarily by epigenetic silencing, unlike many other tumor suppressors, such as p53, that are inactivated mainly by deletion and mutation [23] . Molecular epidemiology studies have investigated the relationship between DNA hypermethylation-induced inactivation of RUNX3 and individual risk of cancer development in various organs, including the lungs, pancreas, urinary bladder, and gastric cancers [12,[24][25][26] .…”
Section: Discussionmentioning
confidence: 99%